Experimental study on the crush behavior and energy-absorption ability of circular magnesium thin-walled tubes and the comparison with aluminum tubes. (1st June 2018) - Li, Zhigang; Yang, Haifeng; Hu, Xiongwei; Wei, Jifei; Han, Zhitong
Highlights: Axial crush tests were performed on magnesium (Mg) and aluminum (Al) circular tubes. Effect of length/diameter ratio on crushing modes of Mg and Al tubes was studied. Changing law of crashworthiness of Mg and Al tubes with impact speed was revealed. Effect of induced feature on crashworthiness of Mg and Al tubes was investigated. Abstract: In this study, a series of axial crush tests were performed on AZ31B magnesium and A6063 aluminum thin-walled circular tubes to investigate the influence law of the failure mode and energy absorption capacity dictated by length/diameter (L/D) ratio, compression speed, and induced features as well as their difference. In general, the magnesium tubes absorbed energy mainly by fracture while the aluminum tubes absorbed energy by plastic yielding with folding generated. With increasing L/D, the failure mode of magnesium tube generally tended to change from a splitting mode with relative good crashworthiness to a bi-tube slicing mode with inferior crashworthiness and, finally to an Euler mode that nearly lost its crashworthiness, whereas, for the aluminum tubes, the ring or diamond or ring & diamond mixed mode was observed, with crashworthiness parameters changing very slightly. The compression speed has more obvious effect on the energy-absorption increment of magnesium tube than that of the aluminum tube. The SEA (specific energy absorption, which is defined as the energy absorbed per unit mass of the crushed tubes) of the magnesium tube was lower than that of the aluminum tubes at quasi-static condition regardless of the failure modes; however, it outperformed the aluminum tube at the compression speed equal or greater than 0.1 m/s. The induced features characterized in this study exhibited an alternating trend between the original deformation/failure mode and an inferior mode, which did not facilitate the load-carrying and energy absorption of both the magnesium and aluminum tubes.